Plan de desarrollo 2008-2011 fundamentos - Medellín, Alcaldía de (La Sociología en sus Escenarios, 2010)
Abstract. The Plan is focused in a strategy to diminish the poverty and to improve the quality of life of sectors of the population that been have excluded from the dynamic ones and the benefits of the development. Medellin must approach to the problem of 1 ' 107,469 people in poverty situation and vulnerability, who represent 49% of the population of Medellin (Its corresponds to the number of people classified in level 1 and 2 of the SISBEN to December of 2007). Within this group of people in poverty situation, the Plan sets out to guarantee conditions adapted to the 125,877 children and smaller children of 6 years, that represent 71.3% of the children and children of the city, with the purpose of to eliminate the poverty traps and to prevent its intergenerational reproduction. Between years 2004 and 2008, the Municipality of Medellin worked in the implementation of a model of oriented public management to goals, which contributes to the fortification of an Administration is transparent and participating, whose emphasis turns around the efficient allocation of resources public and to the fulfillment of the government objectives. The definitive consolidation of this model nevertheless requires of the political will and the decided effort of several Administrations, as well as of the commitment of the citizenship to exert its role in the social control of way responsible and with an ample sense for the joint responsibility. In a period of four years (2008 - 2011), the Municipality sets out to fortify and to extend the reach of this new style of management, which constitutes a substantial change in the culture and the processes of the public institutions. It is tried to extend the emphasis that traditionally has occurred to the processes and when what doing, by the emphasis in the profit of benefits. This implies organizational changes, in the information systems, the processes, the form to evaluate the performance of the servants, and in the form as the government and the citizenship are related. Like support to the model of management by goals, a system of pursuit to the Plan of Development will be implemented that, in coherent form with the foundations of the Plan. Resumen. El Plan se focaliza en una estrategia para disminuir la pobreza y mejorar la calidad de vida de amplios sectores de la población que han estado excluidos de las dinámicas y los beneficios del desarrollo. Medellín debe abordar el problema de 1'107.469 personas en situación de pobreza y vulnerabilidad, que representan el 49% de la población de Medellín (corresponde al número de personas clasificadas en nivel 1 y 2 del SISBEN a diciembre de 2007). Dentro de este grupo de personas en situación de pobreza, el Plan se propone garantizar unas condiciones adecuadas a los 125.877 niños y niñas menores de 6 años, que representan el 71,3% de los niños y niñas de la ciudad, con el fin de eliminar las trampas de pobreza e impedir su reproducción intergeneracional. Entre los años 2004 y 2008, el Municipio de Medellín trabajó en la implementación de un modelo de gestión pública orientada al logro de resultados, el cual contribuye al fortalecimiento de una administración transparente y participativa, cuyo énfasis gira en torno a la asignación eficiente de recursos públicos y al cumplimiento de los objetivos de gobierno. La consolidación definitiva de este modelo requiere sin embargo de la voluntad política y el esfuerzo decidido de varias administraciones, así como del compromiso de la ciudadanía para ejercer su rol en el control social de manera responsable y con un sentido amplio de la corresponsabilidad. En el cuatrenio 2008 - 2011, el municipio se propone fortalecer y ampliar el alcance de este nuevo estilo de gestión, el cual constituye un cambio sustancial en la cultura y los procesos de las instituciones públicas. Se pretende trascender el énfasis que tradicionalmente se le ha dado a los procesos y al qué hacer, por el énfasis en el logro de beneficios. Esto implica cambios organizacionales, en los sistemas de información, en los procesos, en la forma de evaluar el desempeño de los servidores, y en la forma como el gobierno y la ciudadanía se relaciona. Como soporte al modelo de gestión por resultados, se implementará un sistema de seguimiento al Plan de Desarrollo que, en forma coherente con los fundamentos del Plan.